Pengaruh Komite Audit Terhadap Kinerja Keuangan Perusahaan Dengan Dewan Komisaris Sebagai Variabel Intervening - Yunita Kurnia Shanti (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
This study aims to examine the effect of the audit committee on the company's financial performance with the board of commissioners as an intervening variable in manufacturing companies in the consumer goods sector in 2016-2018. The population in this study is the manufacturing companies in the consumer goods sector which are listed on the Indonesia stock exchange in the 2016-2018 period. The sampling method uses purposive sampling, which is a sampling technique with certain considerations or criteria. The number of samples obtained that can be processed is 90 samples. The data analysis method used is path analysis which has previously gone through a classic assumption test, testing is done directly and indirectly. The results of this study indicate the audit committee directly and significantly influences the company's financial performance. Both audit committees have an indirect and significant effect on the company's financial performance with the board of commissioners as an intervening variable. This shows that the calculation of the beta coefficient directly is greater than the indirect beta coefficient which is 0.230>0.05552. This result means that the board of Commissioners variable cannot be an intervening variable of the audit committee on financial performance, because the effective supervisory function in evaluating the results of internal and external audits on the presentation of financial statements becomes the role of the audit committee.